1989
DOI: 10.1002/mde.4090100213
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach to corporate social responsibility programme formulation

Abstract: This paper proposes a quantitative methodology to support executive decision making in the allocation of scarce resources to competing demands in the area of Corporate Social Responsibility (CSR). The Analytical Hierarchy Process is used to translate subjective value judgements such as preferences and perceptions into quantitative measures. These utility values are then used to isolate the factors which determine the choice among the competing CSR programmes. The approach is illustrated with two case studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this model, principles of social responsibility have been framed at the institutional, organizational, and individual levels, and environmental assessment, stakeholder management, and issues management have been coined as processes of social responsiveness, and finally social impacts, programs, and policies have been proposed as outcomes of CSP. In Contrast, Brice and Wegner (1989) have proposed an Analytical Hierarchy Process Model using quantitative methodology to support executive decision making in the allocation of scarce resources to competing demands in the area of CSR. In this model, subjective value judgments such as preferences and perceptions have been translated into quantitative measures, i.e., utility values.…”
Section: Measurement Of Corporate Social Performance (Csp)mentioning
confidence: 99%
“…In this model, principles of social responsibility have been framed at the institutional, organizational, and individual levels, and environmental assessment, stakeholder management, and issues management have been coined as processes of social responsiveness, and finally social impacts, programs, and policies have been proposed as outcomes of CSP. In Contrast, Brice and Wegner (1989) have proposed an Analytical Hierarchy Process Model using quantitative methodology to support executive decision making in the allocation of scarce resources to competing demands in the area of CSR. In this model, subjective value judgments such as preferences and perceptions have been translated into quantitative measures, i.e., utility values.…”
Section: Measurement Of Corporate Social Performance (Csp)mentioning
confidence: 99%
“…The earliest publication in the research sample dates back to 1989 (Brice & Wegner, 1989). Nevertheless, the constant presence of case studies among the CSR publications indexed in Scopus has been reported since 2003.…”
Section: Research Productivitymentioning
confidence: 99%
“…The AHP worked well and a truss bridge was recommended, and it is successfully meeting the selection criteria. Brice and Wegner (1989) used the AHP methodology in two case studies of large South African corporations and their stakeholder management since the change of power there. They observed an increase in prioritisation given to stakeholders requiring corporate social responsibility programs (i.e.…”
Section: Ahp Applications In Generalmentioning
confidence: 99%